Promoting the War Effort : Robert Horton and Federal Propaganda, 1938-1946 - Lee, Mordecai, 1948- (Book collections on Project MUSE., 2012)
Though historians have largely overlooked Robert Horton, his public relations campaigns remain fixed in popular memory of the home front during World War II. Utilizing all media-including the nascent technology of television-to rally civilian support, Horton's work ranged from educational documentary shorts like Pots to Planes, which depicted the transformation of aluminum household items into aircraft, to posters employing scare tactics, such as a German soldier with large eyes staring forward with the tagline "He's Watching You." Iconic and calculated, Horton's campaigns raise important ques.